Bioactive constituents of Terminalia ferdinandiana Exell: A pharmacognistic approach towards the prevention and treatment of yersiniosis - Wright, Mitchell Henry; Arnold, Megan Sarah Jean; Aldosary, Huda; Sirdaarta, Joseph; Greene, Anthony Carlson; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Yersinia enterocolitica is a facultatively anaerobic gram negative bacterium which contaminates meat products causing the acute gastrointestinal disease yersiniosis. Terminalia ferdinandiana (Kakadu plum, gubinge) is an Australian fruit with an extremely high antioxidant capacity. It was used therapeutically by the first Australians and has documented antiseptic properties against an extensive panel of bacteria. Despite this, it has not been tested for the ability to inhibit the growth of Y. enterocolitica. Methods: T. ferdinandiana fruit and leaf extracts were extracted by maceration and the extracts were investigated by disc diffusion assay for growth inhibi- tory activity against a clinical strain of Y. enterocolitica. The MIC values of the extracts were determined to quantify and compare their efficacies. Toxicity was determined using the Artemia franciscana nauplii bioassay. The most potent extracts were investigated using non-targeted GC-MS analysis (with screening against a compound database) for the identification and characterisation of individual components in the crude plant extracts. Results: Solvent extractions of T. ferdinandiana leaf and fruit displayed good growth inhibitory activity in the disc diffusion assay against Y. entero- colitica. The methanolic T. ferdinandiana leaf and fruit extracts, as well as the fruit ethyl acetate extract, were particularly potent growth inhibitors, with MIC values of 372, 123 and 285 µg/mL respectively. The aqueous and ethyl acetate leaf extracts also displayed good growth inhibitory activity against Y. enterocolitica, albeit with higher MIC values (588 and 1100 µg/mL respectively). All other extracts were either low efficacy, or completely devoid of growth inhibitory activity. All T. ferdinandiana leaf and fruit extracts were either nontoxic (LC50 values <1000 µg/mL) or of low toxicity in the Artemia franciscana bioassay. Non-biased GC-MS phytochemical analysis of the methanolic extracts putatively identified and highlighted several compounds that may contribute to the ability of these extracts to inhibit the growth of Y. enterocolitica. Conclusion: The lack of toxicity and the potent growth inhibitory bioactivity of the T. ferdinandiana fruit and leaf methanolic extracts against Y. enterocolitica indicates their potential as me- dicinal agents in the treatment and prevention of yersiniosis.
Keywords: Kakadu plum; gubinge; Yersinia enterocolitica; Enterobacteria- ceae; antioxidant; antibacterial; terpenoids; GC-MS; metabolomic profile.